El centro y la periferia, una aproximación empírica a la relación entre Lima y el resto del país - Aguilar Andía, Giovanna; Camargo, Gonzalo (Economia, 2004)
The main purpose of this paper is to evaluate empirically the economic relation betweenLima and some departments of the country by estirnating the effect of shocks affectingLima's growth over the rates of growth of the remaining departments. We do notpretend to describe the mechanisms of transmission but to identificate the negative andpositive effects of shocks coming from Lima, considered 'Yhe center", over the rest of departments,considered "the periphery". It will be used the Autorregresive Vector Model inits Moving Average representation (VMA), in which the endogenous variables are Lima'srate of growth, the rate of growth and the rate of inflation of a periphery department. It isassumed that these variables are affected by shocks of demand and supply originated inthe center and the periphery. In order to ortogonalize the estimated error variance-covariancematrix we will use the Blanchard and Quah decomposition, in which innovations oraggregate demand shocks have no effect over the product on the long run.